The Restructuring (Systemization) of Local Government under the Constitution of the Republic of South Africa, 1996 - Heyns, C.H. (Christof H.) (University of Pretoria, 2013)
Thesis (Doctor Legum (Public Law))--University of Pretoria, 2006.